2006
DOI: 10.1002/hep.21097
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal mucosal alterations in rats with carbon tetrachloride-induced cirrhosis: Changes in glycosylation and luminal bacteria

Abstract: Spontaneous bacterial peritonitis is a major cause of mortality after liver cirrhosis. Altered permeability of the mucosa and deficiencies in host immune defenses through bacterial translocation from the intestine due to intestinal bacterial overgrowth have been implicated in the development of this complication. Molecular mechanisms underlying the process are not well known. In order to understand mechanisms involved in translocation of bacteria, this study explored the role of oxidative stress in mediating c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 45 publications
3
30
0
2
Order By: Relevance
“…Liver cirrhosis can induce functional alterations in the intestine [13,14] and kidney [15] due to oxidant stress, which has also been demonstrated in mice cardiac cells after bile duct ligation [34]. Our data now show that elevations in protein carbonyl and malondialdehyde are evident in the heart before development of frank cirrhosis in the liver after TAA administration.…”
Section: Oxidative and Nitrosative Stress In The Heart Precedes Develsupporting
confidence: 76%
See 1 more Smart Citation
“…Liver cirrhosis can induce functional alterations in the intestine [13,14] and kidney [15] due to oxidant stress, which has also been demonstrated in mice cardiac cells after bile duct ligation [34]. Our data now show that elevations in protein carbonyl and malondialdehyde are evident in the heart before development of frank cirrhosis in the liver after TAA administration.…”
Section: Oxidative and Nitrosative Stress In The Heart Precedes Develsupporting
confidence: 76%
“…Oxygen free radicals have been implicated in the pathogenesis of toxic liver injury [12], and oxidative stress during liver cirrhosis is responsible for intestinal and renal damage [13][14][15]. Oxidative stress has been suggested to be involved in cardiac dysfunction in the cirrhotic heart [16], and an increase in lipid peroxidation markers has been demonstrated in the kidney, brain and heart of rats with cholestatic liver disease suggesting oxidative damage to different organs [17].…”
Section: Introductionmentioning
confidence: 99%
“…Carbon tetrachloride (CCl 4 ) causes tissue injury especially in hepatocytes by the formation of reactive trichloromethyl radicals [23]. Trichloromethyl radical reacts with molecular oxygen to form trichloromethylperoxyl radical and oxidizes lipid molecules by hydrogen abstraction especially in hepatocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, bacterial translocation has been recognized as a possible major contributor to the development of systemic infection and multiple organ dysfunction after shock, mechanical trauma, or thermal injury, as well as in ICU patients. Numerous experimental studies using animal models of trauma [3], thermal injury [4,5,6], hemorrhagic shock [7, 8], intestinal obstruction [9], obstructive jaundice [10, 11], and liver cirrhosis [12, 13] have shown that bacterial translocation occurs commonly in various situations. In humans, there is also increasing evidence for bacterial translocation under specific conditions as listed in table 1.…”
Section: Does Bacterial Translocation Occur In Humans?mentioning
confidence: 99%